Cellular and Molecular Mechanisms of Pristimerin in Cancer Therapy: Recent Advances - Chen, Run-Ze; Yang, Fei; Zhang, Min; Sun, Zhi-Gang; Zhang, Nan (Frontiers in Oncology, 2021)
Seeking an efficient and safe approach to eliminate tumors is a common goal of medical fields. Over these years, traditional Chinese medicine has attracted growing attention in cancer treatment due to its long history. Pristimerin is a naturally occurring quinone methide triterpenoid used in traditional Chinese medicine to treat various cancers. Recent studies have identified alterations in cellular events and molecular signaling targets of cancer cells under pristimerin treatment. Pristimerin induces cell cycle arrest, apoptosis, and autophagy to exhibit anti-proliferation effects against tumors. Pristimerin also inhibits the invasion, migration, and metastasis of tumor cells via affecting cell adhesion, cytoskeleton, epithelial-mesenchymal transition, cancer stem cells, and angiogenesis. Molecular factors and pathways are associated with the anti-cancer activities of pristimerin. Furthermore, pristimerin reverses multidrug resistance of cancer cells and exerts synergizing effects with other chemotherapeutic drugs. This review aims to discuss the anti-cancer potentials of pristimerin, emphasizing multi-targeting biological and molecular regulations in cancers. Further investigations and clinical trials are warranted to understand the advantages and disadvantages of pristimerin treatment much better.